1995
DOI: 10.1038/bjc.1995.449
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin 1, a novel antineoplastic agent and protein kinase C activator, induces human myalgia and muscle metabolic defects: a 31P magnetic resonance spectroscopic study

Abstract: Summary Bryostatin 1, a novel antineoplastic agent and protein kinase C (PKC) activator, has been found to induce myalgia (muscle pain) 48 h after administration in clinical trials. This is the dose-limiting toxicity and has restricted the duration of therapy in phase I trials. To investigate the mechanisms and try to increase toleration of the drug, we studied calf muscle metabolism of 14 patients at rest and during exercise and subsequent recovery using 31P magnetic resonance spectroscopy (MRS) before and 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In the absence of nifedipine, bryostatin caused a decrease in proton efflux from the muscle and a decrease in mitochondrial function (Hickman et al, 1995). These changes could be explained as resulting from bryostatin-induced vasoconstnction in vivo, as has been observed in the isolated perfused rat heart (K Clarke and P Hickman, personal communication).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In the absence of nifedipine, bryostatin caused a decrease in proton efflux from the muscle and a decrease in mitochondrial function (Hickman et al, 1995). These changes could be explained as resulting from bryostatin-induced vasoconstnction in vivo, as has been observed in the isolated perfused rat heart (K Clarke and P Hickman, personal communication).…”
Section: Discussionmentioning
confidence: 79%
“…Nifedipine had no independent effect on proton efflux, but the previously reported reduced proton efflux following bryostatin infusion (Hickman et al, 1995) was abolished by pretreatment with nifedipine (Table II) After the initial studies (study 1), subjects were started on slow release nifedipine 10mg twice daily orally throughout the remainder of the protocol. One week following commencement of nifedipine, subjects were examined again (study 2), after which the patient received an infusion of bryostatin (25 Mg m-2).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Its aetiolo5v is unknown. and appears to be a direct drug effect on muscle (Hickman et al 1995: Thompson et al 1996. Other studies have shown that the myalgia is not reversed by nifedipine.…”
Section: Resultsmentioning
confidence: 99%